Dietary Patterns in Association With Hypertension: A Community-Based Study in Eastern China - Wang, Cuicui; Zheng, Yanmin; Zhang, Ya; Liu, Dong; Guo, Li; Wang, Bo; Zuo, Hui (Frontiers in Nutrition, 2022)
Objective: We aimed to explore the association between dietary patterns and hypertension based on a community-based survey in Suzhou, Eastern China. Methods: This cross-sectional analysis was undertaken from the subset of Suzhou Food Consumption and Health State Survey in 2018-2019. Adults aged ≥ 18 years were invited to participate in this survey. Dietary intake was collected by 24-h dietary recall and weighing method over three consecutive days (including two weekdays and one weekend day). Dietary patterns were defined using factor analysis. Association between the dietary patterns and hypertension was examined by multivariable logistic regression models with adjustment for covariates. Moreover, sensitivity analysis was used to reinforce our findings. Results: A total of 2718 participants were included in the final analysis. Rice-vegetable pattern, fast food pattern, fruit-dairy pattern and wheat-meat pattern were identified. We observed that the fruit-dairy pattern was inversely associated with hypertension after adjustment for all the covariates (OR = 0.55; 95% CI: 0.40, 0.75; P = 0.002). The association between the wheat-meat pattern and hypertension was attenuated and became statistically nonsignificant in sensitivity analyses. The other two patterns were not significantly associated with hypertension (P > 0.05). Conclusions: The fruit-dairy pattern was associated with a lower prevalence of hypertension among the Chinese adults. Our findings further emphasize the important role of optimal diet combination in the prevention of hypertension.